Effect of Isolated Mesophilic Bacterial Consortium on the Composting Process of Pressed–Shredded Empty Oil Palm Fruit Bunch - Lai, Jia; Chua, Han; Saptoro, Agus; Ang, Ha Ming (Springer Science+Business Media, 2013)
Empty fruit bunch (EFB) is one of the main solid wastes generated from palm oil mills. Incineration and mulching have been employed traditionally to process EFB. This method of waste treatment becomes a great concern since burning of EFB is prohibited by environmental regulation, and moreover, the process is costly and unsustainable. Composting of EFB has the potential to replace the conventional methods used. Composting is a bioconversion process involving microbial activity that transforms biomass wastes into useful organic substrate or fertilizer. In this work, an experimental study was carried out to investigate the composting of pressed–shredded empty fruit bunch (EFB) with mesophilic bacterial consortium as composting microorganisms. The bacterial consortium was isolated from empty fruit bunch compost and cultivated under mesophilic condition at 35 °C. The experiments were conducted under ambient conditions, and the process was carried out for a duration of 40 days. Changes in moisture content, pH and temperature during composting process were evaluated. The composting temperature varied from 26.5 to 28 °C, and the final pH of compost was found to be 6.91. The moisture of compost fluctuated between 60 and 80% over the period of study. At the end of composting period, an average of 54% loss in the dry weight for EFB was observed when the isolated mesophilic bacterial consortium was added during the composting process.